Parallel Meeting Chat Guide for Moderators and Participants - Gillett, Sharon; Bragg, Danielle; Baym, Nancy; Bergmann, Rachel; Sarkar, Advait; Rintel, Sean; Sellen, Abigail (Microsoft Research, 2021)
This report provides guidelines for meeting moderators and meeting participants using parallel chat in video meetings for work. It draws on a large-scale (N=849) study of Microsoft employees’ experiences of all-remote meetings during COVID-19. The report covers chat issues before, during, and after the meeting. There is an emphasis on accessibility practices for ensuring that parallel chat is inclusive of people with a range of abilities. The report draws on our 2021 CHI Late Breaking Work research paper: "The promise and perils of parallel chat in video meetings for work." ACM Reference Format: Sharon Gillett, Danielle Bragg, Nancy Baym, Rachel Bergman, Advait Sarkar, Abigail Sellen, and Sean Rintel. 2021. Parallel Meeting Chat Guide for Moderators and Participants: Drawing on Findings from Microsoft Employees During Covid-19. Technical Report 2021-02-FOW-SIM2. Microsoft Research.